Polychaete worms (Annelida) collected in Golfo Dulce, during the Victor Hensen Costa Rica expedition (1993/1994) - Dean, Harlan K. (1996)
A total of forty seven species of benthic polychaetes belonging to twenty five families have been identified from bottom samples taken in Golfo Dulce, Costa Rica, by the RV Victor Hensen. Only those stations collected in waters less than 100 m depth contained polychaetes. The major feeding type of these polychaete species was surface deposit feeding with slightly fewer species recognized as carnivores. Comparison of the species identified from the RV Victor Hensen material with those of the RV. T.G. Thompson material collected in 1969 reveals very few that are common to the two studies, indicating that the polychaetes of Golfo Dulce are probably quite diverse and poorly known. An estimated total of eighty five species of polychaetes have been identified from Golfo Dulce in the two studies.